Role of Social Media in Environmental Crisis - Daffina', Roberto (Indonesian Journal of Social and Environmental Issues (IJSEI), 2024)
The current environmental and social crises are directing human beings toward extinction. This has come about after using an economic development model for hundreds of years that has depleted natural resources that can no longer be reproduced and caused the extinction of thousands of plant and animal species. Through this study, the development of information and communication technology has been compared over time with environmental degradation and conservation actions. Separate growth paths that have found a point of contact with climate marches and have continued together for more than a decade. The message among humans is increasingly passing through social channels enjoyed by mobile devices. Some generic user data were analyzed on a global and continental level, while the demographic and territorial characterization of Italian users was explored in depth. Through this article, we aim to show that it is important to use social media for the involvement of people in addressing environmental crises. The increasing use of these communication tools allows through targeted messages their active involvement.